Boosting the high-temperature discharge performance of nickel-hydrogen batteries based on perovskite oxide Co-coated LaFeO3 as proton insertion anode. (19th April 2022) - Ren, Kailiang; Zhang, Lu; Miao, Jiajia; Zhao, Jiajin; Yang, Shuqin; Fu, Yaokun; Li, Yuan; Han, Shumin
Abstract: Perovskite oxide LaFeO3 with low cost has received increasingly attention as a new type anode material for proton insertion, however, the poor conductivity restricts its discharge ability for widespread application. Herein, to improve the conductivity of the LaFeO3, we prepare an in-situ cobalt coated LaFeO3 by carbon reduction during which the gas generated reduces the agglomeration of LaFeO3 at nucleation stage. The coated cobalt significantly improves the electrical conductivity of LaFeO3, thereby increasing both the rates of charge transfer and hydrogen diffusivity during discharge, which subsequently boost the discharge performance of LaFeO3 . Study shows that the Co-coated LaFeO3 electrode with 15 wt% delivers remarkably increased discharge capacity of 260.2 mAh g −1 at 60 °C, in contrast to 162.5 mAh g −1 for pure LaFeO3 . Moreover, the LaFeO3 -15 wt% Co also serves superior long cycle-life, maintaining 41.8% after 100 cycles, which is twice of the pure LaFeO3 . Highlights: Co coated in situ greatly improves the discharge capacity of LaFeO3 . The CO2 gas generated in the process of material synthesis inhibits the agglomeration of LaFeO3. Co coating improves the conductivity of the LaFeO3 material itself. The high rate discharge ability of LaFeO3 –15 wt%Co reaches up to 15.82%. LaFeO3 –15 wt%Co delivers superior capacity retention of 41.8% at the 100th cycle.